(untitled) (Research, Society and Development, 2023)
The present research has as its object the study of the right to health in the Brazilian system. In the course of the research, the phenomenon of Judicial Activism will be analyzed, a controversial theme, which consists of the possibility of a judge being able to force the representative functions - Legislative and Executive - to create public policies, able to implement social rights, such as health. After this theme, the Theory of the Reserve of the Possible and the Principle of the Existential Minimum will be discussed. These, inherent to the issue of social rights, constitute a counterpoint to one another, in the sense that, respectively, they seek to limit and immediately enforce fundamental rights. Besides the discussion of the theorized concepts inside of Constitutional Rights, it seeks to demonstrate the practical application of the debate about the access whit in the problematic of obtaining high cost´s medicines through a social clamor against the state, in several situations by the Health´s Judicialization. The themes presented are relevant and constitute the subject of several critical positions, since, in practice, fundamental rights, almost always, seek to be protected through the jurisdiction, and not through the political path, as, as a rule, they should be.